2019
DOI: 10.1111/vde.12721
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum macrophage migration inhibitory factor (MIF) and correlation with severity and pruritus scores in client owned dogs with atopic dermatitis

Abstract: Background -Atopic dermatitis (AD) is a common inflammatory skin disease of dogs. Macrophage migration inhibitory factor (MIF) initiates pro-inflammatory cytokine release in human AD and serum concentrations are correlated with disease severity.Hypothesis -Canine serum MIF concentrations are increased in dogs with AD and correlate with clinical lesion and pruritus scores.Animals -Client owned dogs (n = 49) diagnosed with AD and 17 healthy, unaffected control dogs were used for the study.Methods and materials -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…2 Furthermore, the lesional severity scores of dogs with cAD did not correlate with the serum concentrations of other cytokines, including IL-17, IL-31 and macrophage migration inhibitory factor. 39 Therefore, serum TARC concentrations appear to be a more accurate marker than previously studied biomarkers and correspond well with the lesional severity of cAD.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…2 Furthermore, the lesional severity scores of dogs with cAD did not correlate with the serum concentrations of other cytokines, including IL-17, IL-31 and macrophage migration inhibitory factor. 39 Therefore, serum TARC concentrations appear to be a more accurate marker than previously studied biomarkers and correspond well with the lesional severity of cAD.…”
Section: Discussionmentioning
confidence: 77%
“…In studies on cAD, although total IgE concentrations were significantly higher in dogs with cAD than in healthy controls, they did not correlate with clinical severity according to the Canine Atopic Dermatitis Lesion Index 2 . Furthermore, the lesional severity scores of dogs with cAD did not correlate with the serum concentrations of other cytokines, including IL‐17, IL‐31 and macrophage migration inhibitory factor 39 . Therefore, serum TARC concentrations appear to be a more accurate marker than previously studied biomarkers and correspond well with the lesional severity of cAD.…”
Section: Discussionmentioning
confidence: 88%
“…It has been shown to play a role in human AD 64,65 . MIF levels were found to be increased in atopic dogs, apparently not correlated with clinical scores nor pruritus, and thus the clinical relevance of these findings is unknown 66 …”
Section: The Aberrant Immune Responsesmentioning
confidence: 97%
“…64,65 MIF levels were found to be increased in atopic dogs, apparently not correlated with clinical scores nor pruritus, and thus the clinical relevance of these findings is unknown. 66 Another recent study evaluating potentially useful peripheral markers showed decrease expression of micro-RNA gene markers (PIAS1, RORA and SH2B1) and an increased expression of the phosphodiesterase 4D gene in peripheral blood mononuclear cells in addition to differential expression of cytokines in dogs with AD in comparison to healthy controls. 67 Again, the clinical relevance of these findings needs to be further evaluated to see how relevant these changes are for AD and how much they simply reflect a state of inflammation.…”
Section: The Role Of the Microbial Composition Of Atopic Skinmentioning
confidence: 98%
“…Consistently, lacrimal fluids collected from patients with severe AD contain a significantly greater concentration of this cytokine in comparison to those with a milder disease (304). This factor is also elevated in animals with AD (305). When neutralized, experimental AD is ameliorated (306).…”
Section: Macrophage Migration Inhibitory Factormentioning
confidence: 73%